Conversion of ortho and para nuclear spin isomers of methanol studied by internal axis method - Li-Sha Ma; Zhen-Dong Sun (Results in Physics, 2021)
Quantum statistics of identical nuclei in molecules gives rise to nuclear spin isomers. Except for methanol (CH3OH) that has internal rotation (i.e., torsion), all the studied molecules so far have overall rotational symmetry. Methanol does not rotate around the overall rotational symmetry axis but the methyl group axis. The identical nuclei in the methyl group produce a specific type of nuclear spin isomers of the ortho-CH3OH and para-CH3OH in methanol. Conversions between these two spin isomers have been observed in the experiment and a theory based on the rho-axis method (RAM) for partially explaining their conversions has been developed by us recently. However, besides RAM the internal axis method (IAM) is a classical method commonly used by many researchers and the coupling of the angular momenta between torsion and overall rotation in methanol can be completely separated from each other in the IAM. In this paper, as a series work we present a general theoretical model about conversion of ortho–para methanol using the IAM based on quantum relaxation theory. The expressions of the ortho–para state-mixing strengths induced by the nuclear spin–spin and nuclear spin–rotation interactions have been analytically deduced and numerically calculated. We found that the ortho–para states-mixings and ortho–para conversion can be induced by all these two intramolecular interactions whereas the nuclear spin–rotation interaction plays a major role. The conversion rate at temperature 300 K and pressure 1 Torr summed over eight ortho–para level pairs with gaps less than 2.7 GHz is calculated to be 1.4 × 10−2 s−1, which is close to the measured value of 2.1 (3) × 10−2 s−1, indicating the quantum relaxation is the leading process in the spin isomers conversions of methanol and suggesting our theory to be valid for other gaseous methanol-like molecules having torsion tunneling of symmetrical group. The most probable gateways in methanol for collision-induced population transfers are found to be levels-pairs in the ground-state A–E species of (υt J, K, p) = (0, 24, 4, 1)−(0, 25, 2, 1) by nuclear spin–spin coupling, (0, 22, 5, p)−(0, 21, 6, −1) and (3, 34, 1, 0)−(3, 35, 0, 1) by nuclear spin–rotation coupling.